Targeting the NTSR2/TrkB oncogenic pathway in chronic lymphocytic leukemia - Ikhlef, Léa; Yassine, May; Chandouri, Boutaîna; Rivière, Léa; Naves, Thomas; Dmytruk, Natalya; Gachard, Nathalie; Jauberteau, Marie-Odile; Gallet, Paul-François (Scientific reports, 2024)
Current therapies that target the B-cell receptor pathway or the inhibition of anti-apoptotic proteins do not prevent the progressive forms of chronic lymphocytic leukemia (CLL), have low long-term efficacy and are subject to therapeutic resistance. Deciphering the mechanisms of leukemic cell survival and searching for new specific targets therefore remain major challenges to improve the management of this disease. It was evidenced that NTSR2 (neurotensin receptor 2), through the recruitment of TRKB (tropomyosin related kinase B), induces survival pathways in leukemic B cells. We have investigated the therapeutic potential of this protein complex as a new target. The binding domain of NTSR2 and TRKB was identified and a peptide targeting the latter was designed. The peptide binds TRKB and efficiently decreases the interaction of the two proteins. It is also effectively internalized by CLL-B cells in which it notably affects Src family kinase signaling and anti-apoptotic proteins levels. It demonstrated a cytotoxic effect both in vitro on the MEC-1 cell line and ex vivo on a cohort of 30 CLL patients. Altogether, these results underline the therapeutic potential of the NTSR2/TRKB protein complex as a target in CLL and open new perspectives for the development of targeted therapies.